1964
DOI: 10.1111/j.1751-1097.1964.tb08171.x
|View full text |Cite
|
Sign up to set email alerts
|

ACTTON SPECTRA OF PHYTOCHROME IN VITRO*

Abstract: ATTENTION to phytochrome and phytochrome-controlled physiological responses has been devoted chiefly to the red and far-red regions of the visible spectrum. Radiation of shorter wavelengths, however, also has an influence on plant development through its action on phytochrome.('. ' ) The absorption spectra of the two forms of phytochrome show, in addition to the major absorption bands in the red and far-red regions, minor bands in the blue and near u.v.@$ which are also effective in the photoconversions of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
112
1
1

Year Published

1965
1965
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(119 citation statements)
references
References 6 publications
5
112
1
1
Order By: Relevance
“…The spectral parameters of purified phytochrome determined in recent studies (3,8,15,17,18) are different from those reported by Butler et al (2). Two factors are probably responsible for these differences.…”
contrasting
confidence: 51%
See 4 more Smart Citations
“…The spectral parameters of purified phytochrome determined in recent studies (3,8,15,17,18) are different from those reported by Butler et al (2). Two factors are probably responsible for these differences.…”
contrasting
confidence: 51%
“…Two factors are probably responsible for these differences. The phytochrome samples used in the old studies (1,2) contained a high proportion of proteolytically degraded 60 kD phytochrome, while most recent preparations consist mainly of undegraded ('native') 124 kD phytochrome (8,17,18). Recent preparations are purer, as suggested by values of the A665/A280 specific absorbance ratio for Pr much higher than that reported for the old phytochrome preparations (1,2,14).…”
mentioning
confidence: 84%
See 3 more Smart Citations